Assessment of Risk Factors and Prevalence of Musculoskeletal Disorders in Coppersmiths of Kerman City by RULA Method - Saman Dastaran; Naser Hasheminejad; Chiman Saeidi; Farzan Madadizadeh (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: Copper casting jobs are the ones in which musculoskeletal disorders have high prevalence due to repetitive movements and awkward postures. So, this study was conducted to assess the prevalence of risk factors and musculoskeletal disorders among Coppersmiths of Kerman in 2014 using RULA. Methods: This study was a descriptive – analytical research. In order to assess risk factors of musculoskeletal disorders, working status of 10 coppersmiths was studied using RULA method in Kerman. Information needed to determine the prevalence of musculoskeletal disorders was collected through Nordic questionnaire and then analyzed by SPSS 16 software. Results: The highest prevalence of musculoskeletal disorders was observed at the waist, with a prevalence of 90%. Following waist, the most common symptoms were related respectively to knee (80%), neck (70 %), wrist (60%), ankles and shoulders (30 %), as well as elbows and thighs (10%). Conclusion: The findings of this study showed that musculoskeletal disorders have high disorders in coppersmiths and risk levels of these disorders is higher than moderate.